Analisis Dampak Penggunaan Internet terhadap Budaya dan Tradisi Bagi Remaja Desa Anjir Serapat - Saiffullah Darlan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This research aims to find out the impact of the use of the internet through mobile phones by the teenagers of the village on the culture and traditions in Anjir Serapat. The research subjects were teenagers who settled in Handil. The data collection techniques through observation, interviews, and documentation. The observations are carried out diligently and strengthened by triangulation, as well as discussions with teenagers. The data collected were analyzed following qualitative research procedures starting from data collection, data condensation, data appearance, and verification and conclusion. The results of the research found that: First, the positive impact is the work can be done more efficiently and effectively in processing business results, then that opportunities for welfare can be done in a short time; teenagers are encouraged to be more advanced and dare to open the isolation caused by the culture and the kolot (old-fashioned); the young people are encouraged to improve the quality of their education, which at first they only had a low level of education such as elementary schools/madrasah, and junior high schools, then they continue going to senior high school. The other negative impact is the culture and customs that already exist in the community began to fade. As a result, many teenagers have left their habit that is always obeyed in the community; many teenagers are no longer obedient to their parents; liquor that used to be considered taboo and illicit goods in the community is now considered normal and there are even teenagers using it.